Gas-Containing Paralabral Ganglion Cyst of the Shoulder: A Case Report. Issue 2 (April 2015) - Sakamoto, Yoshihiro; Kido, Akira; Inoue, Kazuya; Tanaka, Yasuhito
Abstract : Case: A thirty-three-year-old woman presented with right shoulder pain and moderate atrophy of the infraspinatus muscle, with grade-4 (of 5) external rotation strength. Magnetic resonance imaging showed a gas-containing ganglion cyst. Surgical excision and arthroscopic evaluation were performed. The extra-articular arthroscopic view of the ganglion showed bubbles within the mucous material. One year after surgery, she had pain-free, normal range of motion and normal strength of the affected shoulder. Conclusion: We report a rare case of a gas-containing ganglion cyst that originated in the posterosuperior glenohumeral capsule and caused entrapment of the suprascapular nerve.